PENJADWALAN MATAKULIAH MENGGUNAKAN ALGORITMA GREEDY (STUDI KASUS PENJADWALAN SEMESTER GANJIL 2017-2018 INFORMATIKA ITENAS) - Yasmin Math Khader; Youllia Indrawaty Nurhasanah; Afriyanti Dwi Kartika (Universitas Widyatama, 2018)
Arranging college subject becomes one of the problem for the institute. Limited of class rooms, lecturer time that should be adjusted, many courses should be attended by college student cause arranging college subject should carefully arranged. Making manual schedule need more time and obstructing lectures. The purpose of this study is to implement greedy algorithms so that the results of scheduling lectures that have no clash, class capacity and number of students can adjust. Greedy algorithm is a computational algorithm to find the shortest distance, from the theory then diadposi into computational algorithms to find the lowest value in the combination of scheduling a class. By applying the greedy algorithm to the system, the system can generate class schedules without clashes, class capacity and number of students can adjust. The output of this system is the course schedule stored in the calendar.